Julius Nyangaga of the International Livestock Research Institute on outcome mapping - Nyangaga, J. (KMIC, 2011)
Julius Nyangaga discusses his experience with projects which use Outcome Mapping to measure knowledge sharing among diverse stakeholders and shares his reflections on how OM can be used to capture knowledge uptake.